Development of Learning Media Integrated Module Application Based on Socio-Scientific Issues Enriched Augmented Reality on Electrolysis Cell Material - Kurniawan, Dhimas Bagus; Sumari, Sumari (Orbital: The Electronic Journal of Chemistry, 2024)
This study aims to develop learning media integrated module applications based on socio-scientific issues enriched by augmented reality on electrolysis cell material and test the feasibility and validity of chemistry learning media products developed. The research method used is research and development (R&D) using the 3D model adopted from the 4D model developed by Thiagrajan et al. (1974: 5), which consists of 3 stages, namely: define, design, and development. This research is only limited to the development stage. The instruments used in this research are validation and readability test questionnaires. The validators consisted of 2 people, namely one lecturer from the Chemistry Department of the State University of Malang and one chemistry teacher from SMAN 2 Batu, as media and material experts. The readability test was conducted on 29 undergraduate students of the Chemistry Education class 2022 at the State University of Malang, assuming they had taken the subject during class XII in senior high school. The results showed that the validity of the material and media included very feasible criteria with 98.24% and 96.81%, respectively, in addition to the average of all aspects of the readability test assessed having a percentage of 91.77%.